2017
DOI: 10.4103/1995-705x.221226
|View full text |Cite
|
Sign up to set email alerts
|

The burden of truncus arteriosus in an Urban City in Africa: How are we fairing?

Abstract: Background:The true incidence of truncus arteriosus in underdeveloped countries is difficult to determine. This is due largely to underreporting as a result of nonavailability of technologically advanced facilities to make definitive diagnosis prenatally. There is a lack of data on the profile and outcome of patients with persistent truncus arteriosus (PTA) in Nigeria. This study aims to document the demographic characteristics, mode of presentation, indications for echocardiography, associated anomalies, aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…At admission, 89.7% of patients had class IV heart failure, with comparable figures between the two groups. Furthermore, 62% of patients had chest examination findings suggestive of congestion, indicating congestive heart failure, again consistent with studies in Ethiopia and other low-resource settings where children with RHD often present at advanced stages [6,9,[15][16][17]. However, the proportion of class IV heart failure in our study was significantly higher than reported in other Ethiopian studies (13.6%) and studies from Timor-Leste (78% for all heart failure classes combined) and India (36.4% for all heart failure classes combined) [11][12][13].…”
Section: Discussionsupporting
confidence: 84%
“…At admission, 89.7% of patients had class IV heart failure, with comparable figures between the two groups. Furthermore, 62% of patients had chest examination findings suggestive of congestion, indicating congestive heart failure, again consistent with studies in Ethiopia and other low-resource settings where children with RHD often present at advanced stages [6,9,[15][16][17]. However, the proportion of class IV heart failure in our study was significantly higher than reported in other Ethiopian studies (13.6%) and studies from Timor-Leste (78% for all heart failure classes combined) and India (36.4% for all heart failure classes combined) [11][12][13].…”
Section: Discussionsupporting
confidence: 84%
“…At admission, 89.7% of patients had class IV heart failure, with comparable gures between the two groups. Furthermore, 62% of patients had chest examination ndings suggestive of congestion, indicating congestive heart failure, again consistent with studies in Ethiopia and other low-resource settings where children with RHD often present at advanced stages [6,9,[15][16][17]. However, the proportion of class IV heart failure in our study was signi cantly higher than reported in other Ethiopian studies (13.6%) and studies from Timor-Leste (78% for all heart failure classes combined) and India (36.4% for all heart failure classes combined) [11][12][13].…”
Section: Discussionsupporting
confidence: 81%
“…Whereas other regions report lower prevalence of 2.4% of the cases of CHD,[6] truncus arteriosus marginally followed tetralogy of Fallot at 5%. Mean age at the diagnosis was 5 months of the 165 children with a female preponderance.…”
Section: Persistent Truncus Arteriosusmentioning
confidence: 89%